Occurrence, Distribution and Farmers' Perceptions of Cassava Diseases in Gabon, Central Africa - (:unkn) unknown (My University, 2023)
Aims: In order to identify and assess the level of cassava diseases in farms present in Gabon, disease surveys were carried out across the country in 2021 and 2022. Methodology: The method used is based on administration of questionnaire to cassava growers, supplemented by the recognition of disease symptoms on 30 randomly selected plants in farms. Results: Some 201 cassava growers were interviewed, 84.04% (n=169) of them were women and 15.92% (n=32) men. Nearly 65.41% of the farmers interviewed had a primary school education and were aged between 51 and 55. The majority of these producers had farming as their main activity (89.73%). The results showed the occurrence of five cassava diseases in the study area: cassava mosaic (Im = 60.22%; Sm = 2.95), anthracnose (Im = 19.45%; Sm = 3), leaf necrosis (Im= 9.95%; Sm = 2.71), bacteriosis (Im = <1%; Sm = 3), and root rot (Im = <1%; Sm = 2.61). Among these diseases, mosaic was the most frequently observed in the provinces surveyed. Its incidence was lowest in Estuaire (38.40%) and highest in Ogooué-Ivindo (71.36%) and Ogooué-Maritime (71.76%). Anthracnose incidence was lowest in Moyen-Ogooué (4.05%) and highest in Haut-Ogooué (36.50%). For leaf necrosis, Woleu-Ntem (0.71%) and Ogooué-Ivindo (31.11%) recorded the lowest and highest incidence respectively. Conclusion: In order to control these cassava diseases, it is important to initiate and implement awareness campaigns and training workshops for growers to encourage them to adopt good farming practices.
Keywords: African Research